2022
DOI: 10.1099/mgen.0.000831
|View full text |Cite
|
Sign up to set email alerts
|

Population genomics of pneumococcal carriage in South Africa following the introduction of the 13-valent pneumococcal conjugate vaccine (PCV13) immunization

Abstract: Streptococcus pneumoniae is a major human pathogen responsible for over 317000 deaths in children <5 years of age with the burden of the disease being highest in low- and middle-income countries including South Africa. Following the introduction of the 7-valent and 13-valent pneumococcal conjugate vaccine (PCV) in South Africa in 2009 and 2011, respectively, a decrease in both invasive pneumococcal infections and asymptomatic carriage of vaccine-type pneumococci were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 26 publications
7
8
0
Order By: Relevance
“…We were able to refine this model to look at the fitness of individual serotypes and found a wide range of fitness across serotypes. Among NVTs serotypes 15A, 35B, and 8 had the greatest fitness advantage post-PCV (Figure S12-14) concordant with what has been previously described (13,14,26). We also found that shifts in lineage fitness result in changing patterns of spread.…”
Section: Fitness Impact Of Vaccine and Antimicrobial Resistancesupporting
confidence: 89%
See 3 more Smart Citations
“…We were able to refine this model to look at the fitness of individual serotypes and found a wide range of fitness across serotypes. Among NVTs serotypes 15A, 35B, and 8 had the greatest fitness advantage post-PCV (Figure S12-14) concordant with what has been previously described (13,14,26). We also found that shifts in lineage fitness result in changing patterns of spread.…”
Section: Fitness Impact Of Vaccine and Antimicrobial Resistancesupporting
confidence: 89%
“…We found that the implementation of PCV7 in 2009 and PCV13 in 2011 was associated with a substantial disruption in the patterns of circulating serotypes, consistent with what has been observed elsewhere (4,13,24,25). By 2014, serotypes included in PCV13 represented 33.2% of all isolates in our dataset, down from 85.0% in the pre-vaccine era (Figure 4A).…”
Section: Fitness Impact Of Vaccine and Antimicrobial Resistancesupporting
confidence: 88%
See 2 more Smart Citations
“…For isolates with resistance that formed clusters -which suggests emerging resistant lineages -the estimated tMRCA for the cluster with penicillin resistance in GPSC33 is 1937 (95 % HPD 1927(95 % HPD -1946 and that for the cluster with cotrimoxazole resistance in GPSC46 is 1922 (95 % HPD 1821-1988). The tMRCA of lineages is between the 1920s and the 1930s, coinciding with the discovery of penicillin and cotrimoxazole, but prior to their widespread use [17,18]. The tMRCA confidence intervals for the cluster with resistance to cotrimoxazole are wide, and antimicrobial use may have contributed to the emergence of this cluster.…”
Section: Gpsc33 Lineage Consistsmentioning
confidence: 99%